How molecular allergology can shape the management of allergic airways diseases. Issue 2 (April 2020) - Caimmi, Davide; Manca, Enrica; Carboni, Elena; Demoly, Pascal
Abstract : Purpose of review: In allergy, personalized medicine passes through the assessment of molecular allergens sensitization profiles. Such technique may help to better diagnose and treat patients suffering from allergic respiratory diseases. Recent findings: Different laboratory tests are available today to assess sensitization to molecular allergens, from singleplex assays, to unspecific, screening multiplex assays, mainly performed through microarrays or macroarrays. It is important to collect both results from specific IgE toward allergen extracts and toward molecular allergens, to collect the most complete information on the patient's profile, and therefore to highlight genuine sensitization, and exclude cross-reaction and sensitization because of pan-allergens. Being able to know the exact molecular sensitization profile of the patient, also helps predicting the possible evolution of the disease, and targeting the most appropriate allergen immunotherapy treatment to prescribe. Summary: Even though a cost-effective analysis of running multiple assays in allergic patients has not been performed yet, such technique proved to be more efficient in detecting the appropriate treatment in each patient and in analyzing the true sensitization profile in patients suffering from allergic rhinitis, conjunctivitis, and asthma.